Peningkatan Keberdayaan Kelompok Nelayan “Lautan Sejahtera” Lawallu Barru Melalui Penggunaan Teknologi Penangkapan Ikan Dan Pemasaran Online - Tabsir, Muhammad Kusnady; Azis, Putri Athirah; Kadir, Rachmawaty (Universitas Pahlawan Tuanku Tambusai, 2024)
This community service is carried out with the aim of providing training to fishermenwho are members of the Lautan Sejahtera Fishermen's Group in Lawallu Village, Barru Regency. The implementation of this service consists of 3 main activities, namely first, training on the use of fishing equipment technology, namely flying drones integrated with fish finders and GPS, second, training on calculating ice needs and packaging fish and Online Marketing Training. It is hoped that this training can be a solution to reduce the need for fuel when fishing, thereby reducing fishermen's operational costs. Catches last longer and fishermen can market products online to expand the market and thus increase income. This training, as a form of community service, was attended by 15 members of the Lautan Sejahtera Fishermen's Group.